Corporate governance regulation: a practice theory perspective. Issue 1 (2nd January 2023) - Nakpodia, Franklin; Adegbite, Emmanuel; Ashiru, Folajimi
ABSTRACT : Employing Bourdieu's practice theory, this paper explores factors that influence corporate executives' behaviour towards corporate governance regulation. Drawing insights from a weak institutional environment (Nigeria) and relying on a qualitative research methodology (semi-structured interviews with 31 executives), this research uncovers how nine nuanced situational and cultural field factors determine executives' regulatory response to the severity of punishment, the certainty of penalties, and the cost–benefit compliance considerations. The study further explains how sequential rationalisation between the severity and certainty of punishment contributes to the regulatory apathy that executives exhibit. Theoretically, this study demonstrates how practice theory components (habitus, capital, and field) blend to establish executives' regulatory practice.